Toward 3D Solid-State Batteries via Atomic Layer Deposition Approach - Liu, Jian; Zhu, Hongzheng; Shiraz, Mohammad H. A. (Frontiers in Energy Research, 2018)
3D solid-state batteries are receiving great attentions as on-board power supply systems for small-dimension devices, due to their high power and energy densities. However, the fabrication of 3D solid-state batteries has been a formidable challenge due to the limitation of conventional thin-film techniques. Recently, atomic layer deposition (ALD) has emerged as a powerful approach toward 3D solid-state batteries, because of its exclusive advantage of coating uniform, pinhole-free, and conformal functional thin films on high-aspect-ratio substrates. Herein, we review the most recent progress in the utilization of ALD for fabricating 3D solid-state batteries. Specifically, two aspects will be highlighted: the development of glassy solid-state electrolytes (especially lithium phosphorus oxynitride), and the fabrication of 3D solid-state batteries in half-cell and full-cell configurations via ALD approach. Based on this, the perspectives for further research will be discussed.